The Effect of Probiotics Probio_Fmubb on The Growth of Catfish (Clarias sp.) in Fixed Net Cage Systems - Rangga, Muhammad Yusup; Adibrata, Sudirman; Artika, Dina; Pinari, Pinari (Politeknik Kelautan dan Perikanan Karawang, 2023)
The increase in aquaculture activities has made most people interested in working on it. Catfish is one of the cultivation commodities that are in great demand by the public. This study aims to analyze the growth of probiotic catfish (Clarias sp.) in soil ponds with the KJT system. The research was conducted from September to November 2022 at the pond of Mr. Fitra, a member of the Pokdakan Mina Berkah Mandiri, Balunijuk Village, Bangka Belitung. The research method includes calculating the growth of catfish and testing water quality which is accompanied by PP No. 22 years 2021. Fish growth shows a positive allometric pattern, meaning that weight growth is more dominant than length growth. This is thought to be a positive effect of the probiotic Probio_FmUBB on catfish growth and pond water quality. Water quality is sufficient to support the growth of catfish, especially the main parameters such as temperature, pH, and DO. Known water quality values such as temperature parameters 27-30oC, pH 6.05, and DO 5.03 mg/L affect catfish growth. Feeding full pellets is very supportive of positive allometric growth patterns and optimal catfish growth. Suggestions can be developed for catfish enlargement by Pokdakan with persistence while raising fish.